The effect of music technology on skill acquisitions based on gender in Faculty of Music at Universiti Teknologi MARA / Khairul Hazwan Musa - Musa, Khairul Hazwan (2015)
Studies on gender have offered many reasons for the differing skill acquisitions in music technology. The introduction of music technology is important because as a constructivist learning pedagogy, its approach emphasizes learning by doing via direct students' engagement in technology. The purpose of the research is to investigate the gender differences in proficiency skills in music technology, to examine the gender differences in terms of accessibility for learning and to explore gender differences of music technology application based on training-received. The data collected to support the research is through a quantitative method by surveying. The research was carried out on students from the music faculty at UiTM. The data was analyzed using SPSS. The findings have suggested that no gender differences in skill acquisitions in music technology.